Healthcare facility-onset, healthcare facility-associated Clostridioides difficile infection in Veterans with spinal cord injury and disorder. (2nd September 2020) - Evans, Charlesnika T.; Fitzpatrick, Margaret; Ramanathan, Swetha; Kralovic, Stephen M.; Burns, Stephen P.; Goldstein, Barry; Smith, Bridget; Gerding, Dale N.; Johnson, Stuart
Abstract: Objective: To describe the burden and risk of healthcare facility-onset, healthcare facility-associated (HO-HCFA) Clostridioides difficile infection (CDI) in Veterans with spinal cord injury and disorder (SCI/D). Design: Retrospective, longitudinal cohort study from October 1, 2001–September 30, 2010. Setting: Ninety-four acute care Veterans Affairs facilities. Participants: Patients with SCI/D. Outcomes: Incidence rate of HO-HCFA CDI. Methods: Rates of CDI were determined, and crude unadjusted incidence rate ratios (IRRs) and 95% confidence intervals (CIs) were calculated. Multivariable Poisson random-effects regression analyses were used to assess factors independently associated with the rate of CDI. Results: 1, 409 cases of HO-HCFA CDI were identified. CDI rates in 2002 were 13.9/10, 000 person-days and decreased to 5.5/10, 000 person-days by 2010. Multivariable regression analyses found that antibiotic (IRR = 18.79, 95% CI 14.09-25.07) and proton-pump inhibitor (PPI) or H2 blocker use (IRR = 7.71, 95% CI 5.47-10.86) were both independently associated with HO-HCFA CDI. Exposure to both medications demonstrated a synergistic risk (IRR = 37.55, 95% CI 28.39-49.67). Older age, Northeast region, and invasive respiratory procedure in the prior 30 days were also independent risk factors, while longer SCI duration and care at a SCI center were protective. Conclusion: Although decreasing, CDI rates in patients with SCI/D remain high. Targeted antimicrobial stewardship and pharmacy interventions that reduce antibiotic and PPI/H2 blocker use could have profound benefits in decreasing HO-HCFA CDI in this high-risk population.